2013
DOI: 10.1007/s11356-013-1786-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, socioeconomic, and maternal health determinants of placental transfer of organochlorine compounds

Abstract: The aim of this study was to relate placental transfer, quantified by the cord to maternal serum concentration ratio (C/M), of five organochlorine pesticides (OCP) hexachlorobenzene (HCB), β-hexachlorocyclohexane (β-HCH), γ-hexachlorocyclohexane (γ-HCH) , p,p'-DDT, p,p'-DDE and 15 polychlorinated biphenyl (PCB) congeners (28, 52, 101, 105, 114, 118, 123+149, 138+163, 153, 156+171, 157, 167, 170, 180, and 189) to anthropometric, socioeconomic, and maternal health characteristics. We included into the study 1,13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The respective equations, based on median HCB cord serum/maternal serum concentration ratios of 0.265 for wet weight and 1.097 for lipid adjusted HCB concentrations (Patayová et al, 2013), are as follows: 1.097 Maternal serum HCB level(ng/glipid) = Cord serum HCB level(ng/glipid) 0.265 Maternal serum HCB level(ng/Lserum) = Cord serum HCB level(ng/Lserum)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The respective equations, based on median HCB cord serum/maternal serum concentration ratios of 0.265 for wet weight and 1.097 for lipid adjusted HCB concentrations (Patayová et al, 2013), are as follows: 1.097 Maternal serum HCB level(ng/glipid) = Cord serum HCB level(ng/glipid) 0.265 Maternal serum HCB level(ng/Lserum) = Cord serum HCB level(ng/Lserum)…”
Section: Resultsmentioning
confidence: 99%
“…However the relationship between the concentration of the compounds in milk and the fetus is not straightforward. In our paper, we derive parameters necessary for conversion of breast milk HCB concentrations into cord serum levels, both, wet weighed and lipid adjusted, based on the extant published literature and our own data (Patayová et al, 2013; Lancz et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patayová et al (2013)) have demonstrated the highest 4,4′-DDE levels in the Europe zone with 393.348 ng/g lipid. Although 4,4′-DDT exposure seemed to be lower than in Spain, the determined value was 17.427 ng/g lipid.…”
Section: Discussionmentioning
confidence: 99%